Strengthened Magnetoresistive Epoxy Nanocomposite Papers Derived from Synergistic Nanomagnetite-Carbon Nanofiber Nanohybrids - Gu, Hongbo (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.